Impact of Symbolic Interactionism, Pragmatism and Social Constructionism on Communication and Media Practice - Udoudom, Uduak; Bassey, Borono; George, Kufre; Etifit, Samuel (Darul Yasin Al Sys, 2024)
As communication technologies and media platforms continue to evolve, there is a growing need to re-examine the theoretical paradigms underpinning our understanding of human interaction and meaning-making. This research elucidates the enduring relevance of three sociological perspectives—Symbolic Interactionism, Pragmatism, and Social Constructionism—for making sense of contemporary communication landscapes. Employing a qualitative meta-synthesis methodology, we analysed 50 academic articles and book chapters discussing applications of these perspectives within communication and media studies. Our analysis reveals how core concepts from each tradition—including symbolic meaning-making, practical consequences of communication, socially constructed representations—contain explanatory power for grasping new communication patterns and challenges brought by digitalization. Researchers apply Symbolic Interactionist notions of symbolic cues and improvised self-presentations to study computer-mediated communication and social media self-constructions. Pragmatist views on communicative actions as tools for desired ends inform critical analyses of fake news propagation and disinformation campaigns. Social Constructionist emphasis on mass media representations shaping shared realities has expanded to deconstructions of algorithmically-curated information environments. By elucidating these and other linkages, our study aims to revitalize engagement with forgotten or overlooked theoretical foundations in order to advance communication scholarship and enhance reflexivity within emergent media ecosystems. We conclude that integrating insights from Symbolic Interactionism, Pragmatism, and Social Constructionism remains vitally important, both for scholarly aims of explaining reality and practical aims of consciously shaping it.